The Pathogenicity Of Velogenic Viscerotropic Newcastle Disease Virus In The Bursa Of Fabricius - Othman, Fauziah (1993)

(untitled)
Newcastle disease (ND) is one of the important poultry diseases in Malaysia. Although the disease is controlled through vaccination programmes, outbreaks have been reported in vaccinated flocks from time to time. The success of any vaccination programme depends on several factors and one of them is the integrity of the immune system. The bursa of Fabricius is an important organ of the immune system which is responsible for humoral immunity against ND. Realising its importance, a study was undertaken to investigate the effect of velogenic viscerotropic Newcastle disease virus (VVNDV) on the bursa of Fabricius. An initial detailed study on the normal structure of the bursa of Fabricius was conducted as a basis for differentiating the effect of VVNDV on the bursa of Fabricius.The effect of VVNDV on the bursa of Fabricius of vaccinated chickens was determined by infecting these chickens via contact with non-vaccinated chickens challenged intranasally with 0. 1 ml of inoculate containing 106 E1DSO of the virus. The damage to the bursa of Fabricius was examined by histological and electron microscopic studies, while virus was detected by isolation, immunoperoxidase staining and transmission electron microscopy. The results showed that VVNDV damaged and replicated in the bursa of Fabricius of vaccinated birds. Grossly, the bursa was swollen, oedematous, haemorrhagic and necrotic. Histopathology showed that there were haemorrhages, oedema, cystic cavities in the follicles containing mucous, necrosis of the follicles and presence of a reduced number of lymphocytes and an increased number of heterophils, macrophages and plasma cells. Scanning electron microscopy showed increased mucous secretion and there was exfoliation of the microvilli. However the follicle-associated-epithelium was intact in the vaccinated challenged birds. In the non-vaccinated challenged birds there was total exfoliation of the epithelium. Viral isolation and immunoperoxidase staining showed evidence of viral replication in the bursa of Fabricius. Ultrastructurally, viral replication was shown by the presence of virus budding and nucleocapsids in the cytoplasm of lymphoid cells and macrophages.